Effects of theoretical contribution, methodological rigor, and journal quality, on the impact of scale development articles in the field of entrepreneurship - Kuskova, Valentina V.; Podsakoff, Nathan P.; Podsakoff, Philip M. (Strategic Entrepreneurship Journal, 2011)
Abstract Despite the widespread belief that empirical studies that are firmly grounded in theory and use valid measures of their focal constructs are more critical to the advancement of science than studies that do not possess these attributes, it is only recently that this belief has begun to be empirically tested. Unfortunately, most of the tests that have been conducted have some limitations. Therefore, the purpose of this study is to examine the effects that an article's theoretical contribution, the rigor of its scale validation procedures, and the quality of the journal in which it is published have on its impact in the field of entrepreneurship. Using expectancy theory as a conceptual framework, we develop and test our hypotheses in a sample of 88 entrepreneurship articles that reported scale development and validation evidence. Our hypotheses were supported in that the results showed that an article's theoretical contribution, methodological rigor, and journal quality significantly predicted the number of citations the article received, even after controlling for article age‐ and author‐related variables. When taken together, the article characteristics and control variables accounted for 66 percent of the variance in article citations. Implications of these findings for researchers in the field of entrepreneurship are discussed. Copyright © 2011 Strategic Management Society.